The Poetry of Du Fu - Warner, Ding Xiang; Kroll, Paul; Warner, Ding Xiang; Kroll, Paul (Berlin, Germany De Gruyter, 2015)
The Complete Poetry of Du Fu presents a complete scholarly translation of Chinese literature alongside the original text in a critical edition. The English translation is more scholarly than vernacular Chinese translations, and it is compelled to address problems that even the best traditional commentaries overlook.The main body of the text is a facing page translation and critical edition of the earliest Song editions and other sources. For convenience the translations are arranged following the sequence in Qiu Zhao$1 (Ban$1 (Bs Du shi xiangzhu (although Qiu$1 (Bs text is not followed). Basic footnotes are included when the translation needs clarification or supplement. Endnotes provide sources, textual notes, and a limited discussion of problem passages. A supplement references commonly used allusions, their sources, and where they can be found in the translation.Scholars know that there is scarcely a Du Fu poem whose interpretation is uncontested. The scholar may use this as a baseline to agree or disagree. Other readers can feel confident that this is a credible reading of the text within the tradition. A reader with a basic understanding of the language of Chinese poetry can use this to facilitate reading Du Fu, which can present problems for even the most learned reader.s
English
Keywords: Classical texts; Literature: history & criticism; Regional studies; Chinese literature; translation